On the genus Mesopontonia Bruce, 1967 (Crustacea: Decapoda: Palaemonidae) in Korea, with the description of a new species - Park, Jin-Ho; De Grave, Sammy; Park, Taeseo (PeerJ, 2020)
Mesopontonia verrucimanus and Mesopontonia kimwoni sp. nov. are recorded from high-latitude temperate waters in Munseom Islet, Jejudo Island, Republic of Korea, with both species collected on gorgonians and sponges by trimix diving between 50 and 75 m depth. Mesopontonia kimwoni sp. nov. is morphologically allied to M. brevicarpus, but can be distinguished by the cutting edges of the fingers of the first chela being entire. Significant morphological variation in the rostrum as well as the second pereiopods is documented in M. verrucimanus, although cytochrome c oxidase subunit I (COI) barcode analysis proves this to be infra-specific variation. A key to species of the genus Mesopontonia is provided.
Keywords: New species; Systematics; Taxonomy; Deep-sea palaemonid shrimp; Korea; Jejudo Island